Comprehensive analysis of circulating miRNA expression profiles in insulin resistance and type 2 diabetes in Qatari population. Issue 1 (31st December 2022) - Errafii, Khaoula; Jayyous, Amin; Arredouani, Abdelillah; Khatib, Hasan; Azizi, Fouad; Mohammad, Ramzi M.; Abdul-Ghani, Muhammad; Chikri, Mohamed
Abstract : Insulin resistance (IR) is type 2 diabetes' hallmark. MiRNAs regulate many target genes that makes them attractive candidates for regulating insulin production, secretion and action. Therefore, we anticipate a change in the circulatory profile of miRNAs in IR subjects compared to normal glucose tolerance subjects. In the present study, we sought to identify the circulating miRNAs associated with IR as biomarkers in Qatari population. The circulating miRNA profile was assessed in a pilot study of healthy volunteers ( n  = 22) whose insulin sensitivity was quantitated by euglycemic hyperinsulemic clamp. Moreover, in the validation phase ( n  = 40) subjects were added including lean and obese T2D. MiR-186 showed a consistent significant increase in insulin resistance subjects compared to NGT in the discovery and validation phase analysis. In addition, intergroup comparison of circulating miRNA pinpointed 2 miRNAs: MiR-122 increased substantially in obese T2D subjects, with diagnostic value to predict obesity in T2D subjects, and let-7b increased significantly in lean T2D subjects. Our results suggest that circulating miRNAs serve as biomarkers for IR, T2D and obesity in Qatari population. Further functional studies are warranted to better identify the targets of these miRNAs and understand the underlying molecular and cellular mechanisms.